Body mass index and body composition scaling to height in children and adolescent - Sochung Chung (Korean Society of Pediatric Endocrinology, 2015)
Childhood obesity prevalence has been increased and known to be related to various diseases and mortality in adult and body mass index (BMI) has been widely used as a screening tool in children with obesity. It is important to understand what BMI is and its limitations. BMI is a measure of weight adjusted for height. Weight scales to height with a power of about 2, is the basis of BMI (weight/height2) as the scaling of body weight to height across adults provides powers rounded to 2. BMI has the advantage of a simple and noninvasive surrogate measure of body fat, but it has limitation in differentiating body fat from lean (fat free) mass and low-moderate sensitivity is problematic for clinical applications. Among overweight children higher BMI levels can be a result of increased either fat or fat-free mass. BMI could be divided into fat-free mass index and fat mass index. Monitoring of the changes in body composition is important as distinguishing changes in each component occur with rapid growth in adolescents as it is occur in concert with changes in the hormonal environment. Reference values for each body composition indexes and chart created with selected percentiles of a normal adolescent population could be helpful in growth assessment and health risk evaluation.